PSXVI-38 Growth performance and nutrient digestibility of grow-finish fed corn-DDGS-soybean meal-based diets without or with a combination of protease and direct fed microbial. - Woyengo, T (J Anim Sci, 2018)
A study was conducted to determine the effects supplementing corn-DDGS-soybean meal-based diets with a combination of protease and direct fed microbial (DFM) on growth performance and apparent total tract digestibility (ATTD) of nutrients of pigs. Eighty pigs (40 barrows and 40 gilts; initial BW = 29.2 ± 1.85 kg) housed in 20 pens of 4 barrows or gilts balanced for BW were fed 2 experimental diets within sex, for a total of 5 pens/diet/sex. The diets were a corn-DDGS-soybean meal-based diet without or with a combination of Bacillus subtilis protease at 5,000 U/kg and 3-strain Bacillus (2 strains of B. amyloliquefaciens and 1 strain of B. subtilis) based DFM at 1.5 E+05 (5.18 log10) cfu/g. The corn-DDGS-soybean meal-based diet was formulated to meet the (NRC 2012) recommended nutrients for grow-finish pigs except for NE, Ca and available P, which were reduced by 50 kcal/kg, 0.09 percentage points, and 0.09 percentage points, respectively. The diets were fed in 3 growth phases based on BW; Phase 1: 30 to 50 kg, Phase 2: 50 to 75 kg, and Phase 3: 75 to 100 kg. Fresh fecal samples were collected on days 26 and 27 of the experiment to determine ATTD. Supplementation of a combination of protease and DFM increased (P < 0.05) the ATTD of DM, GE, N, EE, NDF, ADF and P by 7.0, 8.0, 10.3, 12.6, 50.5, 39.1, and 15.5%, respectively, but did not affect ADG, ADFI and G:F of pigs. In conclusion, supplementation of a combination of protease and DFM to the corn-DDGS-soybean meal-based diet increased nutrient digestibility of growing-finishing pigs but did not effect growth performance, implying that basal diet was not deficient in DE. Thus, basal diets with appropriate low energy values should be developed to optimize utilization of a combination of protease and DFM in diets for pigs.